Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Synthesis and study of calixarene-doped polypyrrole-TiO2/ZnO composites: antimicrobial activity and electrochemical sensors - Waghmode, Babasaheb J.; Husain, Zahid; Joshi, Meenal; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (Journal of Polymer Research, 2016)
The present communication describes the synthesis of an electroactive nanocomposite of calixarene- doped polypyrrole ( PPY) containing an oxide of Ti/ Zn. The additive TiO2/ ZnO serves as an oxidizing agent for the polymerization, thus avoiding the use of hazardous organic solvents while calixarene doping stabilizes the polymer. The materials synthesized herein were characterized by UV- visible spectroscopy, FT- IR spectroscopy, scanning electron microscopy ( SEM), transmission electron microscopy ( TEM), energy- dispersive X- ray spectroscopy ( EDX), X- ray photoelectron spectroscopy ( XPS), and cyclic voltammetry ( CV) of synthesized nanocomposites. It was revealed that the resulting calixarene- doped polypyrrole- TiO2/ ZnO nanocomposite has ( 1) long- time stability, ( 2) significant electrochemical activity for sensing formaldehyde, and ( 3) good antimicrobial activity.

Calixarene based nanocomposite materials for high performance supercapacitor electrode - Waghmode, Babasaheb J.; Soni, Roby; Patil, Kashinath Rangu; Malkhede, Dipalee D. (New Journal of Chemistry, 2017)
A functionalised calixarene {4-Sulphatocalix [6] arene Hydrate (SC6)} stabilises MoS2/partially reduced graphene oxide (rGO) nanosheet. Such stabilised SC6-rGO/SC6-MoS2 and SC6 doped polyaniline (PANI) together forms a nanocomposite hybrid material for supercapacitor electrode. It was fabricated by an in situ polymerization method. Transmission electron microscopy (TEM) results suggest that PANI nanostructures grow homogeneously onto the surfaces of SC6 functionalised MoS2. Calixarene acts as a dopant for PANI as well as a stabiliser for the 2D nanosheets of rGO/MoS2. The characterisation of composites together with basic components was done by using various techniques namely, solid-state FT-IRspectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The electrochemical performance was analysed by cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectrometry (EIS). It was found that the SC6 functionalised MoS2 and SC6 doped PANI formed a uniform nanocomposite. The synthesised composites show high specific capacitance (691 F/g) and good cycling stability during the charge-discharge process when used as supercapacitor electrodes. The improvement in electrochemical performance of composites is assigned to synergistic effect of SC6 stabilised MoS2 and doped PANI. Our investigation highlighted the importance of use of calixarene in composites for above stated supercapacitor performance. The role of calixarene in the present study opens a way for the application of alike materials in the composite supercapacitors for energy storage applications.

In situ grown nickel nanoparticles in a calixarene nanoreactor on a graphene-MoS2 support for efficient water electrolysis - Waghmode, Babasaheb J.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Patil, Kashinath R.; Malkhede, Dipalee D. (Sustainable Energy & Fuels, 2017)
Electrochemical production of hydrogen, facilitated in electrolysers, holds great promise for energy storage and solar fuel production. Catalysis of the oxygen evolution reaction (OER) is a bottleneck of this process. However, the sluggish OER kinetics and the utilization of precious metal catalysts are key obstacles in the broad deployment of this energy technology. We report the preparation and use of an inexpensive GrMoS(2)SC(8)Ni nanocomposite material as a highly effective OER catalyst in an alkaline electrolyte. Experimental investigations have shown that improvements can be realized in the catalytic performance of Ni metal if it is a component of the composite material. We propose an explanation for these enhancements based on a hydrogen acceptor concept. This concept comprises the stabilization of an *-OOH intermediate, which effectively lowers the potential needed for breaking bonds on the surface. Herein, an inexpensive immobilized SC8 layer was used as the nanoreactor to synthesize metallic Ni nanoparticles (NPs) through an in situ redox process. The process was applied to form immobilized NPs on flat and curved 2D surfaces. The outstanding OER performance of Ni NPs could be attributed to their large surface area, efficient mass and charge transport, and high structural stability arising from the unique SC8 cage structure, built on the GrMoS(2) substrate. The GrMoS(2)SC(8)Ni nanocomposite shows the highest activity, exhibiting a 214 mV overpotential at 10 mA cm(-2) (equivalent to 10% efficiency of solarto-fuel conversion) and a Tafel slope of 31 mV dec(-1) in 1 M KOH solution. It further demonstrates high stability as there is no apparent OER activity loss (based on a chronoamperometry test) or particle aggregation (based on SEM image observation) after a 10 h anodization test. The facile preparation method and high efficiency and durability enable this electrocatalyst to be a promising candidate for future large-scale applications in water splitting. Thus, this work opens a new avenue toward the development of highly efficient, inexpensive OER catalysts.

Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction

Graphene-MnO2 composite supercapacitor material accomplished tactically using liquid-liquid and solid-liquid interface reaction techniques - Patil, Sagar H.; Gaikwad, Aarti P.; Waghmode, Babasaheb J.; Sathaye, Shivaram D.; Patil, Kashinath R. (New Journal of Chemistry, 2020)
A novel methodology is described to grow architectures of 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite materials to be used in supercapacitors. The in situ growth of the three-dimensional MnO2 fiber-network over the surface of graphene layers is achieved at the solid-liquid interface. The composite electrode shows good electron and charge transfer, rapid plus reversible faradaic reactions and excellent cyclic ability in electrochemical studies. The electrochemical properties of the as-prepared GNS-MnO2/FTO electrode material were assessed by cyclic voltammetry and galvanostatic charge/discharge tests. The specific capacitance of GNS-MnO2 reaches 683 F g(-1) at a current density of 2.2 A g(-1) and shows excellent cycle stability, retaining 96.9% of its initial capacitance up to 5000 cycles. A coulomb efficiency of about 99% displayed by the GNS-MnO2/FTO electrode is an excellent performance for a desired supercapacitor material. Herein, the charge storage mechanism in 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite is discussed in detail. Furthermore, at an elevated current density of similar to 10.86 A g(-1), a power density of similar to 6.235 kW kg(-1) is achieved, maintaining an energy density of similar to 7.99 kW h kg(-1); thus, it demonstrates promising potential as an electrode material for supercapacitor application.